Ischemia Modified Albumin Can Predict Necrosis at Incarcerated Hernias. Issue 6 (27th November 2013) - Kadioğlu, Hüseyin; Ömür, Dilek; Bozkurt, Süleyman; Ferlengez, Ekrem; Memmı, Naim; Ersoy, Yeliz Emine; Çıpe, Gökhan; Müslümanoğlu, Mahmut
Abstract : Purpose . To evaluate the predictive effect of IMA in incarcerated hernias. Methods . Three groups (n = 7 ) of rats were operated. Group I aimed to mimic incarceration, group II aimed the strangulation, and group III was the sham group. IMA and LDH measurements were made. Results . IMA levels were significantly higher in strangulation mimicking group and IMA levels were normal at postoperative 6th hour in incarceration mimicking group. LDH levels were significantly higher in both incarceration and strangulation mimicking groups. Conclusion . IMA seems to be an effective marker in incarcerated hernias to predict necrosis. But we need further studies to generalise this hypothesis.